Duodenal clamp occlusion aortomesenteric - Czarnevicz, Daniel; Secondo, Gerardo; Radio, Alvaro; Odriozola, Martín; Rossi, Inés; Iacopino, Julio (Cirugía del Uruguay, 1994)
We bring this clinical case as a new contribution to national casuistry and because of its interest, as it corresponds to an infrequent pathology which can appear under serious forms, even with vital risk, a relatively simple therapeutic being possible.